Expanding the clinical phenotype of hereditary BAP1 cancer predisposition syndrome, reporting three new cases. Issue 2 (15th November 2013) - Pilarski, Robert; Cebulla, Colleen M.; Massengill, James B.; Rai, Karan; Rich, Thereasa; Strong, Louise; McGillivray, Barbara; Asrat, Mary‐Jill; Davidorf, Frederick H; Abdel‐Rahman, Mohamed H.
<x xml:space="preserve">Abstract</x> The clinical phenotype of BAP1 hereditary cancer predisposition syndrome (MIM 614327) includes uveal melanoma (UM), cutaneous melanoma (CM), renal cell carcinoma (RCC), and mesothelioma. However, the frequency of the syndrome in patients with UM and the association with other cancers are still not clear. In this study, we screened 46 previously untested, unrelated UM patients with high risk for hereditary cancer for germline mutation in BAP1. We also studied four additional patients with a personal or family history suggestive of BAP1 hereditary cancer syndrome. We identified three patients with germline pathogenic mutations (c.2050 C>T, pGln684*; c.1182C>G, p.Tyr394*, and c.1882_1885delTCAC, p. Ser628Profs*8) in BAP1. Two of these three patients presented with UM and the third with a metastatic adenocarcinoma likely from a hepatic cholangiocarcinoma. Reported family histories included UM, mesothelioma, RCC, CM, and several other internal malignancies. The results of this study confirm the association between germline BAP1 mutation and predisposition to UM, mesothelioma, CM and RCC. However, other cancers, such as cholangiocarcinoma and breast carcinoma may be part of the phenotype of this hereditary cancer predisposition syndrome. In addition, the results support the existence of other candidate genes in addition to BAP1 contributing to hereditary predisposition to UM. © 2013 Wiley Periodicals, Inc.